Implementing flipped learning method in programming course: A case study at UTeM - Shaarani, Ahmad Shaarizan; Bakar, Norasiken; Saifudin, Wan Sazli Nasaruddin; Abdullah, Aida Nasirah; Abd Aziz, Maslita (TextRoad Publication, 2017)
This paper describes the enhancement of engagement model where the new model is adapted and reconstructed from a ‘Model of engaging online students organized around SDT and instructional design elements’. The new suggested model is designed by adding educational theory elements. In addition, we also added two more channel of communication inside the ‘Interaction’ menu which are ‘students-lecturer’ and ‘lecture students’. Those interactions are suggested by previous research who originally created this engagement model. The enhancement model is based on a case study conducted at Universiti Teknikal Malaysia Melaka (UTeM), Malaysia for Programming Technique (using C++ language) subject. The study was conducted for two groups of students, which are ICT and Engineering courses students. For the interaction between students-lecturer and lecturer-students, aside from the forum and activities inside MOOC, the interaction is conducted through social media such as WhatsApp and Facebook.